The electronic press in Algeria within the Organic Law, Media 2012 and the Ethics of the Profession.. See cash - chebri , Mohammed (Journal of Social Sciences and Humanities, 2021)
In this research text, we tackle the subject of the electronic press in Algeria through the organic information law published in 2012, which defines the concept and the role of the electronic press in each written communication service via the Internet intended for public or to a category thereof and published in a professional manner by a natural or legal person, and intended According to many academics in the media field in the online version. In the same context, we will explain the concept of the electronic press, specifying the advantages, the forms and the most important reasons for their use and their relationship with the ethics and deontology of journalists and the right to information, which means the right of the journalist to access the source of information and the right of the audience to receive complete, honest and objective information. On the other hand, we are studying the charter of ethics and professional conduct for Algerian journalists published in 2000, as well as the information code decreed in Algeria in 1990, which is considered to be the birth certificate of the independent press. and medias pluralism. Finally, we will analyze the most important articles of the Organic Law of the Media 2012, which are devoted to defining the concept of ethics in organizing media and professional work for Algerian journalists and everything related to the media and the press.